Sosialisasi Penguatan Karakter Siswa melalui Implementasi Penguatan Delapan Profil Pelajar Pancasila di UPTD SMP N 11 Kota Kupang - Nabu, Adolfina; Klau, Orlince Seran; Longge, Agustina Irawati; Buku, Maria Novita Inya (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Character-strengthening socialization is an important effort to develop students with strong moral values and a Pancasila-oriented mindset in line with the Merdeka Curriculum. This Community Service Program (PKM) was conducted at UPTD SMP Negeri 11 Kupang City and aimed to improve students’ understanding and practice of character values through the eight dimensions of the Pancasila Student Profile. The implementation method involved character socialization activities, including material presentations, interactive discussions, and student reflection sessions. To measure the impact of the program, students’ character understanding was assessed before and after the socialization activities. The results showed an increase in the average score from 68.13 to 85.49, with an N-Gain of 57.61%, categorized as moderate. The most notable improvements were observed in responsibility, cooperation, independence, and critical thinking skills.